Model Partisipasi Masyarakat dalam Pembentukan Peraturan Daerah Menurut Undang -Undang Republik Indonesia Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - King Faisal Sulaiman (Perspektif Hukum, 2017)
This research aims to find out and explain juridical issues about the model used in the formation of regional laws based on Law Number 23 of 2014 and the inhibiting factors of public participation. The ideal alternative model for the preparation of future Regional Regulations. The research method is in the form of normative legal research (legal research) which originates from primary legal materials, secondary legal materials and tertiary legal materials. Statute approach dan conceptual approach. In this study using descriptive- qualitative analysis. Research comes to the conclusion that the 2014 Law Number 23 Year has guaranteed the space for public participation, but the participation model has not been comprehensively regulated. There are various factors inhibiting public participation, such as the political will of policy makers (DPRD and Regional Government), and the attitudes of the public and the media. Finally, a low regulatory factor and a bureaucratic culture that does not provide sufficient space for public participation in the formation of regional regulations. In the future there must be ideal participation models in regional regulations that are clearly regulated in formal regulations, including: First, the public must be actively involved in every stage of the formation of regional regulations. Second, establish permanent cooperation with the formation of regional regulations (DPRD and local government) in providing input on material that will be regulated in the regulations.